Achieving ultralong cycle life graphite binary intercalation in intermediate-concentration ether-based electrolyte for potassium-ion batteries. (30th August 2022) - Lei, Yu; Wang, Jiali; Han, Da; Yuan, Fu; Wang, Huwei; Zhao, Rongyi; Huang, Daqing; Wu, Yiying; Zhang, Biao; Zhai, Dengyun; Kang, Feiyu
Abstract: Controlling graphite intercalation is vital for its use in potassium ion batteries. Prior studies have revealed different intercalation behaviors between a dilute (1 M or less) vs. a concentrated (4 M or higher) ether-based electrolytes: the former forms solvent-co-intercalation while the latter shows binary intercalation. However, no study has been carried out on the intermediate concentrations. In this work, for the first time we report that in an intermediate concentration of electrolyte (2 mol KFSI per kg DME, 2 mol/kg) the electrochemical intercalation of K + ions in graphite anode exhibits an interesting transition from the ternary to binary process with the increasing cycle number. Furthermore, the pre-formed anion-derived solid-electrolyte interphase on graphite anode in highly concentrated electrolyte was rather stable in 2 mol/kg of KFSI/DME electrolyte, and as a result the graphite anode achieved a two-year cycle life with an ultrahigh capacity retention of 96.7% based on binary intercalation. Graphical abstract: Image 1 In intermediate-concentration ether-based electrolyte (2 mol/kg KFSI/DME) the transition of K + ion in graphite anode from ternary to binary electrochemical intercalation upon cycling was reported for the time. Furthermore, in 2 mol/kg of KFSI/DME electrolyte the graphite anode with pre-formed anion-derived SEI achieved a two-year cycle life based on binary intercalation.